Automação do sistema de alimentação de um centro de controle de motores utilizando CLP - SILVA, Samara da (2019)
The present work makes mention of the automation of a feed system of an engine control center with the use of a PLC. The automation project was made necessary, because the system does not have a remote and automatic system of selection of sources for power of the CCM, being necessary now that an operator does the service locally, which wastes time until the arrival, besides the fact Of the system does not have a service that monitors the faults in real time, which makes the system less reliable. With the development of the project is predicted a better reliability of the system, as there will be a remote and automatic system, as well as data obtained in real time from the entire feeding process. In order to carry out the process of automating the system, an HMI was used in addition to the CLP, which will allow the operator to interfere with the operation of the machine, to view operating data, a history of occurrences and other functions.